2017
DOI: 10.56381/jsaem.v1i2.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Motorcycle Braking Performance in Emergency Situation

Abstract: This study was conducted to assess motorcycle braking performance in simulated emergency situation. Braking distances and G- force values (peak) during the braking test of 6 distinct underbone motorcycles of 100-150cc were measured and compared based on different test conditions namely type of brake system (disc and drum), method of braking operation (front and rear brakes) and test load (rider only and rider with pillion). The results indicate that type of braking system and method of braking operation signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The brake distances from each test speed from the dry surface were shown in Table 2 including results from other works of literature. The underbone motorcycles were tested by Ariffin et al (2017) and this study, while high-performance motorcycles were tested by Dinges and Hoover (2018), Dunn et al (2012) and Green (2006). When compared between the underbone and the high-performance motorcycles, it was clear that the high-performance motorcycles achieved higher decelerations.…”
Section: Model Evaluation With Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brake distances from each test speed from the dry surface were shown in Table 2 including results from other works of literature. The underbone motorcycles were tested by Ariffin et al (2017) and this study, while high-performance motorcycles were tested by Dinges and Hoover (2018), Dunn et al (2012) and Green (2006). When compared between the underbone and the high-performance motorcycles, it was clear that the high-performance motorcycles achieved higher decelerations.…”
Section: Model Evaluation With Test Resultsmentioning
confidence: 99%
“…Green (2006) compared the stopping distance performance among total six motorcycles which were equipped with conventional brake systems, combined brake systems (CBS) and anti-lock brake systems (ABS) at some specific speeds. Ariffin et al (2017) compared the braking performance of common motorcycles in the Malaysia market under emergencies. The results from these studies are still not enough to construct the recommended safe stopping distance for a motorcycle which covers all speed range.…”
Section: Introductionmentioning
confidence: 99%
“…A study shows that by using drum brake systems on both wheels, the stopping distance of Honda EX5 is 14.31 m for riders without passengers. Similarly, Yamaha LC that uses disc brakes as the braking system has 13.36 m stopping distance for the same conditions [27]. Braking distance is closely related to braking time.…”
Section: Engineeringmentioning
confidence: 92%
“…Stopping distance is the distance required for a vehicle to from starting braking until it completely stops. Stopping distance depends on several factors: vehicle characteristics (drag coefficient, vehicle weight), speed, and road conditions [26] and the type of brake and vehicle [27]. The stopping distance is directly proportional to the braking time.…”
Section: Engineeringmentioning
confidence: 99%
“…To the best of the author's knowledge, only a few references in the literature examined the braking performance of Malaysian riders. Ariffin et al [11] conducted braking test at the dry path with the speed of 50 km/h using different low cc motorcycles. It was found that the highest deceleration of 0.85g was achieved using both front and rear brakes on the motorcycle equipped with a disc and drum.…”
Section: Introductionmentioning
confidence: 99%